Digital Twin: Potentials for Radio Environment Simulations and Analysis - Hebbar, Chitra Suresh (My University, 2024)
Abstract The rapid evolution of wireless technology, especially, in the context of 5G and beyond, requires innovative solutions to meet the increasing demands of network scaling and complexity. The emergence of network digital twin has marked a significant leap forward in the management of network operations and maintenance. This thesis explores the concept of the network digital twin by performing 3D simulations using advanced tools, with a particular focus on 5G network scenarios. The study unfolds in three phases: initial simulations using the 3D simulator, integration of the tool with OpenAirInterface for core network functionality, and comparative analysis of the 3D simulator result with a standard theoretical model. Most of the work was focused on an indoor scenario, with the possibility to extend later for outdoor environments. The 3D simulator performed better in comparison to the theoretical model. The integration with OpenAirInterface worked successfully in terms of established connection and observed data traffic between base station and user equipment. There are potentials for further improvement by considering additional scenarios and scalability.
Keywords: Keywords: Digital Twin, 3D Simulation, Radio access network, OpenAirInterface.